PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, RETURN ON ASSET, DAN CAPITAL ADEQUACY RATIO TERHADAP PREDIKSI POTENSI FINANCIAL DISTRESS (STUDI EMPIRIS PADA BANK BUMN DI INDONESIA PERIODE 2014-2021) - Regina Agriany Suhartanto; Ventje Ilat; Novi Swandari Budiarso (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
This study aims to determine the effect of Non-Performing Loans, Loan to Deposit Ratios, Return On Assets, and Capital Adequacy Ratios on the Prediction of Potential Financial Distress in State-Owned Banks in Indonesia for the 2014-2021 Period partially or simultaneously. The data in this study are 32 data, namely 8 years of time series data and 4 state-owned banks. The data analysis used in this research is multiple regressions. The results of the study show that (1) Non-Performing Loans (NPL) have an effect on the prediction of potential financial distress in state-owned banks in Indonesia for the period 2014-2021. (2) Loan to Deposit Ratio (LDR) has no effect on the prediction of potential financial distress at state-owned banks in Indonesia for the period 2014-2021. (3) Return on Assets (ROA) has an effect on the prediction of potential financial distress at state-owned banks in Indonesia for the 2014-2021 periods. (4) Capital Adequacy Ratio (CAR) affects the prediction of potential financial distress in state-owned banks in Indonesia for the period 2014-2021. (5) Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return On Assets (ROA), and Capital Adequacy Ratio (CAR) simultaneously affect the prediction of potential financial distress in BUMN Banks in Indonesia for the period 2014-2021 with a value of the coefficient of determination is 97.68%. As for the ability of other variables in explaining the prediction of potential financial distress of 2.32% which is thought to be the market ratio variable, the efficiency ratio (BOPO), and corporate banking investment.